Effect of physical training on exercise-induced hyperkalemia in chronic heart failure. Relation with ventilation and catecholamines. - Barlow, C; Qayyum, MS; Davey, P; Conway, J; Paterson, D; Robbins, P (1994)
BACKGROUND: The exercise-induced rise in arterial potassium concentration ([K+]a) may contribute to exercise hyperpnea and could play a role in exertional fatigue. This study was designed to determine whether the exercise-induced rise in [K+]a is altered in patients with chronic heart failure (CHF) and whether physical training affects K+ homeostasis. METHODS AND RESULTS: We evaluated 10 subjects with CHF (ejection fraction, 23 +/- 3.9%) and 10 subjects with normal left ventricular function (NLVF) who had undergone previous coronary artery graft surgery (ejection fraction, 63 +/- 8.6%). Subjects performed an incremental cycle ergometer exercise test before and after a physical training or detraining program. Changes in [K+]a and ventilation (VE) during exercise were closely related in both groups. Subjects with CHF did less absolute work and had reduced maximal oxygen consumption (VO2max) compared with subjects with NLVF (P < .01). Exercise-induced rises in [K+]a, VE, norepinephrine, lactate, and heart rate were greater at matched absolute work rates in subjects with CHF than in subjects with NLVF (P < .01). However, when the rise in [K+]a was plotted against percentage of VO2max to match for relative submaximal effort, there were no differences between the two groups. Physical training resulted in reduced exercise-induced hyperkalemia at matched submaximal work rates in both groups (P < .01) despite no associated change in the concentration of arterial catecholamines. At maximal exercise when trained, peak increases in [K+]a were unaltered, but peak concentrations of catecholamines were raised (P < .05). The decrease in VE at submaximal work rates after training was not significant with this incremental exercise protocol, but both groups had an increased peak VE when trained (P < .01). CONCLUSIONS: Exercise-induced rises in [K+]a, catecholamines, and VE are greater at submaximal work rates in subjects with CHF than in subjects with NLVF. Physical training reduces the exercise-induced rise in [K+]a but does not significantly decrease VE during submaximal exercise with this incremental cycle ergometry protocol. The reduction in exercise-induced hyperkalemia after training is not the result of altered concentrations of arterial catecholamines. The pathophysiological significance of the increased exercise-induced hyperkalemia in CHF and the mechanisms of improved K+ homeostasis with training have yet to be established.